Do learning approaches matter on setting the time spent for pre-service teachers? - Andri Zainal; Gaffar Hafiz Sagala; Sondang Aida Silalahi (LPMPP Universitas Negeri Yogyakarta, 2021)
This study redefines the research model highlighting the learning approach to investigate the interaction of relevant constructs in the relationship between the learning time spent and academic performance. The subjects of this study were 86 final-year undergraduate students of the accounting education department who had passed the final teaching training program as one of the requirements to become an accounting teacher at the high school and vocational level. In general, time spent has a positive and significant effect on the overall academic performance of the respondents and student groups with the Deep Learning Approach (DLA) and Surface Learning Approach (SLA)'s peers. However, each learning approach has no moderating effect on the relationship between time spent and academic performances. On the other hand, this finding provides an interesting point of view regarding the absence of significant differences in the length of study duration in the two groups of students, which confirms the independence of student learning styles nowadays. Hence, they get more flexible autonomy in improving their academic performance. This research also found that the DLA student group has better academic performance than their SLA counterparts, a finding that is in line with the Social Cognitive Theory and previous research results.